New materials — primary converters of semiconductor measuring cells based on InAs-CdTe system - I. A. Kirovskaya; E. N. Kopylova; E. V. Mironova; A. O. Ekkert; R. V. Ekkert; O. V. Kropotin; V. I. Krasheninin; Yu. I. Matyash (Омский научный вестник)
Using the method developed with reference to the InAs-CdTe system taking into account its condition diagram and the primary bulk physical, physical and chemical properties of the initial binary compounds (InAs, CdTe), the new materials have been obtained — solid solutions (InAs)x (CdTe)x-1. Based on the results of X-ray studies in combination with the results of micro-, electron-microscopic studies, the obtained solid solutions are certified as substitution solid solution with the cubic structure of sphalerite. The acid-base properties of the surfaces of the InAs-CdTe system components have been studied: the pH values of the isoelectric state — pHiso — have been found, indicating that the surfaces belong to a weak-acid region (pHiso<7). The interconnected patterns in changes with the composition of the studied bulk and surface properties, respectively, the relationship between them have been established. The experimentally confirmed forecasts have been made concerning the possibilities of a preliminary assessment of the nature of the ρr concentration dependence and the increased sensitivity of the components surfaces of the studied system to the main gases. The practical recommendations are given on the use of the obtained new materials as primary converters of measuring cells for trace impurities of main gases, in particular ammonia.